Student Learning Motivation in Higher Education: A Self-Determination Theory Perspective - Zaenal Abibin; Charu Hurria (Zabags International Journal of Education, 2026)
Student learning motivation is a critical factor in determining academic success, engagement, and persistence in higher education, particularly within the context of evolving learning environments shaped by digital transformation and socio-cultural diversity. This study aims to analyze student learning motivation through the lens of Self-Determination Theory, with a focus on the fulfillment of the basic psychological needs of autonomy, competence, and relatedness across multiple provinces in Indonesia. The research employs an interpretive qualitative approach with a multi-site design, involving students from diverse regions through in-depth interviews, observations, and focus group discussions. The findings reveal that student motivation is significantly influenced by the level of autonomy in learning, perceived academic competence, and the quality of social relationships within the learning environment. In addition, contextual factors such as the role of instructors, the integration of technology, and institutional policies shape motivational dynamics differently across regions. This study contributes to the theoretical advancement of learning motivation within the Self-Determination Theory framework and provides practical implications for developing more adaptive, inclusive, and context-sensitive learning strategies in Indonesian higher education.